Mental health and well-being of undergraduate dental students: a systematic review - Lim, Shea Lee; Abu Bakar, Noraini; Ahmad Basri, Nadzirah; Mohamed Ludin, Salizar (IIUM Press, 2021)
Mental well-being is the very foundation for emotions, cognition and communication. Mental well-being and mental illness are correlated entities and thus mental well-being should be addressed holistically. Psychological stress, especially chronic stress, can impact one’s health and mental well-being. Dentistry in particular is often said to be highly stressful. This paper aimed to discuss the available literature on mental well-being amongst dental undergraduate students including the prevalence of depression, anxiety, stress, sources of stress, coping strategies and intervention programs. Evidence from this review showed that dental students often had high levels of stress, and also a high prevalence of depression and anxiety which contributed to lower mental well-being in this population. The main sources of stress were mostly academic and clinical factors. Dental students had different coping mechanisms. Social support was found to be a significant factor when coping with stress. Initiatives to bring about improvement of mental well-being and to help students manage stress also showed promising results. Although many studies examined mental health among dental students, most of the studies are cross-sectional in design and were mainly focused on assessing students according to the symptoms they display, e.g. depressed or non-depressed, with very few studies giving focus on the mental well-being of the students. Very little attention was given to students who are 'well' but at risk of developing poor mental well-being. Thus, it is recommended that further research focuses on mental well-being and early intervention measures so as to prevent possible mental health deteriorations.